A new species of the mole cricket genus Gryllotalpa (Orthoptera: Gryllotalpidae; Gryllotalpinae) from India - Prasanna, Vimalanathan Arun; Anbalagan, Sankarappan; Pandiarajan, Jeyaraj; Dinakaran, Sundaram; Krishnan, Muthukalingan (Zootaxa, 2012)
Gryllotalpa krishnani new species (type locality: Tiruchirappalli, India) (Orthoptera: Gryllotalpidae) is described from male, female adults and nymphs. This species is found in the wet soil (10-15cm depth) near to kitchen waste dumping area.